PENGARUH KOMPETENSI GURU DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU DI SMA NEGERI 3 SUNGAI PENUH - Poni Yanita; Irwan Muslim (LPPM - STIE SAKTI ALAM KERINCI, 2023)
This study aims to identify the effect of Teacher Competence and Principal Leadership on Teacher Performance in Sungai Penuh 3 High Schools. This research was conducted to test the presence or absence of relationships or influences between variables, specifically to test the hypothesis in structural equations. The data analysis technique used in this study is the Multiple Linear Regression analysis technique. The results showed that Teacher Competence did not have an influence on Teacher Performance as evidenced by tcount 0.05. Principal's leadership has a significant influence on teacher performance as evidenced by tcount> ttable ie 7.960> 2.008, and a significance value of 0.000 ftabel (137,179> 3.18) and with a significance value of 0,000 <0.05..